From Telephones to AI: A Seventy-Year Bibliometric Analysis of Emergency Call System Research - Bokor, Edita Carmen; Stănilă, Manuel Victoraș; Bărănescu, Mihail; Nen, Madlena (Technium Social Sciences Journal, 2026)
Emergency call systems (ECS) play a vital role in public safety, crisis management, and the organization of emergency response services. Over the last seven decades, these systems have evolved from simple telephone-based communication into complex, digital, and data-driven infrastructures integrating geolocation technologies, artificial intelligence, and multimodal communication. Despite their growing societal relevance, ECS research has not yet been examined through a comprehensive long-term scientific perspective. This study provides a bibliometric and science-mapping analysis of ECS literature published between 1952 and 2025, aiming to identify major research trends, collaboration patterns, and thematic shifts within the field, with particular attention to issues of accessibility and social inclusion. Publications indexed in Scopus and Web of Science were systematically analyzed using descriptive indicators and network-based techniques implemented through the Bibliometrix package in R (version 4.4.0) and VOSviewer. The results show a steady increase in ECS-related research, with accelerated growth after 2010 corresponding to advances in digitalization and intelligent communication technologies. Research output is concentrated primarily in high-income countries and focuses largely on operational efficiency, clinical response, and emergency communication infrastructures. Thematic evolution reveals a transition from early concerns with dispatch organization and response times toward more recent emphases on interoperability, system resilience, and intelligent emergency services. However, accessibility and inclusion, particularly concerning persons with disabilities—remain marginal within the literature, representing only a small fraction of published research. These findings indicate that while ECS research has developed into a multidisciplinary domain spanning public management, health systems, and information technologies, greater attention is required to address social equity, user diversity, and inclusive service design. The study contributes a structured overview of the field’s evolution and highlights future research directions relevant to policymakers, emergency service managers, and scholars concerned with the social dimensions of emergency communication systems.